Transdisciplinarity and climate innovation entrepreneurship in Africa: an assessment using the DCOx framework - Hanlin, Rebecca; Apata, Oluwagbenga; Wandera, Faith Hamala (Frontiers in Sustainability, 2025)
A climate innovation entrepreneur (CIE) is an individual or business that focuses on creating economic value while addressing the climate challenges facing society. Climate innovation entrepreneurship is an increasingly important mechanism in addressing climate change affecting African countries, but is recognised as being extremely difficult to undertake. Given the difficulties of climate innovation entrepreneurship, taking a transdisciplinary approach has been proposed, especially bridging action between research and practice. How to ensure that this takes place in a way that benefits those on the practice side of the bridging action and not just those on the research side requires attention. Moreover, the frameworks that exist have often been developed in the context of the Global North rather than the Global South. This paper attempts to address this issue by examining the experiences of three transdisciplinary research projects focused on climate innovation conducted on the African continent. The qualitative case studies were purposively selected from a list of 13 transdisciplinary projects initially identified. It examines them using the DCOx framework, an analytical framework focusing on the drivers (D) or the rationale of a CIE, the challenges faced by a CIE in operating their business (C) and their desired outcomes or expected results (O). The framework also focuses on the cross-cutting issue of stakeholder engagement (x), which is essential for ensuring successful transdisciplinary research–practice bridging action. The use of the DCOx framework to analyse the three case studies highlighted that co-creation emerged as a cornerstone of success, enabling stakeholders to merge scientific expertise with localised knowledge; tensions between agendas and issues of trust must be addressed while structural barriers and inequalities influence the outcome. The paper ends with a call for more exploration of transdisciplinary projects using the DCOx framework and, importantly, more work to understand if this framework can provide a basis for encouraging and developing more transdisciplinary projects that focus on climate innovation entrepreneurship on the African continent.